Futures’ Trading Practices in Pakistan: A Shariah-based Evaluation - Tahir, Anees (Islamic Banking and Finance Review, 2023)
In Pakistan, stock and commodity futures are frequently traded on the Pakistan Stock Exchange (PSX) and Pakistan Mercantile Exchange (PMX). Futures contract is an agreement between two parties, namely the seller and the buyer, to deliver an asset at a future date against a particular price. It is a contract which comes into effect at a future point of time. A futures contract allows the buying and selling of underlying stocks or commodities at a certain date in the future, at future prices. It is generally settled in cash without delivering or receiving the subject matter or contract. Shariah scholars have divergent opinions about the validity and permissibility of such types of contract. This study aims to explain the Shariah position of these contracts. In particular, this article examines the divergent opinions of Shariah scholars, finance experts and economists on the issue. The prevailing view in modern Islamic jurisprudence is that futures are merely a form of speculation and gambling. Besides, there is no productive economic activity involved in futures trading. It is suggested that, while examining the validity or invalidity of futures a distinction should be made between the purpose of futures trading, as to whether it is for making speculative gains or for a genuine hedging purpose. The distinction should also be made between deliverable futures and cash-settled futures. Futures can be structured on two independent promises as well as wakalah contract.